Risk factors associated with obesity among middle aged adults residing in Bhaktapur, Nepal - Shrestha, Sajeeb; Devkota, Nischal; Shrestha, Rosy (Journal of Chitwan Medical College, 2018)
Introduction: Obesity is a major public health problem worldwide and also in Nepal in which excess body fat has accumulated to the extent that it may have an adverse effect on health, leading to reduced life expectancy and/or increased health problems. Hence, this study was conducted to identify the factor associated with obesity among middle aged adults in Duwakot, Changunarayan. Methods: A descriptive, cross-sectional research design was used among 109 middle aged adults residing in Duwakot, Changunarayan, Bhaktapur. Probability, systematic random sampling technique was used. Semi structured questionnaire was used to collect data by conducting semi-structured interview schedule as well as anthropometric measurement was also taken to calculate the body mass index. Data was analyzed in descriptive and inferential statistics (chi-square test with odd ratio). Results: The prevalence of obesity among middle aged adults was 12.8%. On the basis of statistical analysis, age (p=0.035), ethnicity (p=0.050), alcoholic consumption (p=0.003), sleeping hours at night (p=0.006), physical activity (p-0.014), presence of chronic diseases (p=0.001), used medicine (p=0.001) and family history of obesity (p=0.005) were significant associated factors for obesity among middle aged adult. Conclusion: Prevalence of obesity among middle aged adult was 12.8%. Significant associated factors of obesity were age, ethnicity, alcoholic consumption, sleeping hours at night, physical activity, presence of chronic diseases, used medicine and family history of obesity. So the concerned municipality, health care personnel and related health organization should conduct awareness raising program regarding importance of maintaining normal weight and consequences of obesity in their health.